Ecological shocks and children’s school attendance and farm work in Ghana - Martey, Edward; Etwire, Prince M.; Mockshell, Jonathan; Armah, Ralph; Akorsikumah, Eli (Elsevier, 2023)
Accelerating the education of children and reducing child labor in agriculture remains an important development pathway to preventing intergenerational poverty and achieving the sustainable development goals. While several studies have analyzed the impact of ecological stressors on yield, income, and food security, there is limited understanding of the linkages of prevailing ecological shocks to child education and farm work. In this paper, we examine the effect of ecological shocks of pest and weed invasion on children’s school attendance and working hours on the farm using the seventh round of the Ghana Living Standards Survey (GLSS). We employ a multinomial endogenous switching regression (MESR) model that corrects for selection bias and endogeneity originating from both observed and unobserved heterogeneity. The results show that double shocks (pests and weeds) reduced the number of children attending school by 11% and increased children’s on-farm working hours by 0.75 h. Comparatively, the decline in the number of children attending school due to weed invasion (0.88) is higher than the decline due to pest invasion (0.43). Furthermore, weed invasion increases children’s on-farm working hours by 0.05 h while pest invasion reduces children’s on-farm working hours by 0.08 h. Increasing access to improved agricultural technologies bundled with credit and policies are critical to reducing the threats from ecological shocks and improving farmers’ welfare. To avert the decline in school attendance and children’s working hours requires training farmers to reduce the practice of continuous cropping and to embrace crop rotation and fallow to reduce the spread of pests and weeds.